Poly‐l‐lysine Glycoconjugates Inhibit DC‐SIGN‐mediated Attachment of Pandemic Viruses. (16th July 2021) - Cramer, Jonathan; Aliu, Butrint; Jiang, Xiaohua; Sharpe, Timothy; Pang, Lijuan; Hadorn, Adrian; Rabbani, Said; Ernst, Beat
Abstract: The C‐type lectin receptor DC‐SIGN mediates interactions with envelope glycoproteins of many viruses such as SARS‐CoV‐2, ebola, and HIV and contributes to virus internalization and dissemination. In the context of the recent SARS‐CoV‐2 pandemic, involvement of DC‐SIGN has been linked to severe cases of COVID‐19. Inhibition of the interaction between DC‐SIGN and viral glycoproteins has the potential to generate broad spectrum antiviral agents. Here, we demonstrate that mannose‐functionalized poly‐l ‐lysine glycoconjugates efficiently inhibit the attachment of viral glycoproteins to DC‐SIGN‐presenting cells with picomolar affinity. Treatment of these cells leads to prolonged receptor internalization and inhibition of virus binding for up to 6 h. Furthermore, the polymers are fully bio‐compatible and readily cleared by target cells. The thermodynamic analysis of the multivalent interactions reveals enhanced enthalpy‐driven affinities and promising perspectives for the future development of multivalent therapeutics. Abstract : Mannose‐functionalized poly‐l ‐lysine glycoconjugates efficiently inhibit the DC‐SIGN‐mediated attachment of glycoproteins from pandemic viruses, including SARS‐CoV‐2, to susceptible cells in picomolar concentrations. The compounds are fully biocompatible and represent a promising therapeutic option to combat viral infections. A thermodynamic analysis of the multivalent interactions guides the path towards more potent compounds based on glycomimetic ligands.